Pengaruh Sektor Pariwisata Terhadap Kemiskinan dengan Tingkat Pengangguran Terbuka sebagai Variabel Intervening di Provinsi Bali - Miranti, Putu Gita Suari; Amalia, Layla Fickri (TOBA: Journal of Tourism, Hospitality, and Destination, 2023)
Bali with its mainstay sector in the tourism sector absorbs a high workforce. After the Covid-19 pandemic hit for almost 2 (two) years, Bali's position ranks 19th as a province that has a high unemployment rate in Indonesia. The percentage of poor people in Bali has also increased after the pandemic. This study aims to determine the effect of the tourism sector in Bali on poverty with the Open Unemployment Rate as an intervening variable. The independent variables used are the number of tourist visits, both domestic and foreign, and room occupancy rates which affect the percentage of poor people as the dependent variable, then as the intervening variable, namely the Open Unemployment Rate. The analysis technique used in this research is path analysis. The results of the analysis show that the number of tourist visits and the level of room occupancy directly or indirectly have a significant effect on the percentage of poor people.